Unusually High Levels of CA19-9 Associated with Mature Cystic Teratoma of the Ovary - Madaan, Monika (Hindawi Publishing Corporation, 2014)
Introduction. Mature cystic teratoma is the benign tumor of the ovary. CA19-9 levels, although a marker of pancreatic malignancy, have been found to be raised in large ovarian mature cystic teratomas. Case Report. We report a case of a young female who had unusually high levels of CA19-9 in the blood associated with large ovarian mature cystic teratoma. The levels returned to normal 12 weeks after cystectomy was performed. Conclusion. This case highlights the fact that although raised tumor marker may be associated with a benign pathology thorough evaluation to rule out malignancy still must be done.